Pedagogical Practices of Merdeka Belajar Based Arabic Language Learning Model in Integrated Islamic Elementary Schools - Moh. Nurul Huda; Muhammad Misbakhul Munir; Salsabila Salsabila (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to describe the Merdeka Belajar-based Arabic language learning model at SDIT Gondang Pekalongan, analyze the learning innovations implemented, and identify the problems faced by teachers in its implementation. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research subjects included the principal, Arabic language teachers, and learning documents related to the implementation of the Merdeka Belajar Curriculum. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that the Merdeka Belajar-based Arabic language learning model at SDIT Gondang Pekalongan has not yet been fully aligned with the provisions of the Merdeka Belajar Curriculum because its implementation is still relatively new, having started in the second semester of 2023. Learning administration documents still use the lesson plan (RPP) format of the 2013 Curriculum and have not fully adopted teaching modules in accordance with the Merdeka Belajar Curriculum standards. Nevertheless, the learning process has implemented Project-Based Learning (PjBL) and student-centered learning approaches. The learning innovations carried out by the teachers include the use of enjoyable learning methods, project assignments based on learning themes, interactive learning media, Arabic-themed song adaptations, and Arabic-language videos in the learning process. Meanwhile, the problems encountered by teachers include the lack of training on the Merdeka Belajar Curriculum for Arabic language teachers, difficulties in implementing Arabic language learning according to the demands of the curriculum, and challenges in improving students’ kitabah (writing) and kalam (speaking) skills. This study concludes that the implementation of Merdeka Belajar-based Arabic language learning at SDIT Gondang Pekalongan has moved toward innovative and student-centered learning. However, it still requires strengthening teacher competencies and developing learning tools that are more compatible with the characteristics of the Merdeka Belajar Curriculum.